Extreme thermophilic biohydrogen production from arabinose and glucose - Abreu, A. A. (2013)
Continuous hydrogen production rate from arabinose was significantly higher than from glucose, when higher organic loading rate was used. This fact was associated to higher lactate production in the reactor fed with glucose. The higher concentration of lactate was not a consequence of bacterial community shift, and is likely related to changes in the main metabolic pathways of glucose catabolism.